Similar fertilization rates and preimplantation embryo development among testosterone-treated transgender men and cisgender women. Issue 3 (September 2022) - Israeli, Tal; Preisler, Livia; Kalma, Yael; Samara, Nivin; Levi, Sagi; Groutz, Asnat; Azem, Foad; Amir, Hadar
ABSTRACT: Research question: What are the effects of testosterone treatment on oocyte fertilization and preimplantation embryo development among transgender men who have undergone fertility preservation? Design: A retrospective study was undertaken in a university-affiliated tertiary hospital between April 2016 and November 2021. Embryos were divided into three groups by source: 210 embryos from 7 testosterone-exposed transgender men, 135 from 10 cisgender women who cryopreserved embryos, and 276 from 24 cisgender women who underwent fertility treatment. Statistical analyses compared assisted reproductive technology outcomes between the group of transgender men and both groups of cisgender women. Morphokinetic and morphological parameters were compared between the embryos derived from these three groups. Results: The transgender men (30.2 ± 3.5 years of age) were significantly younger than the cisgender women who cryopreserved embryos (35.1 ± 1.8 years; P   =  0.005) and the cisgender women who underwent fertility treatment (33.8 ± 3.2 years; P   =  0.017). After adjusting for participant age, the fertilization rate was comparable between the transgender men and both groups of cisgender women ( P   =  0.391 and 0.659). There were no significant differences between the transgender men and the cisgender women who preserved fertility in terms of number of cryopreserved embryos (7.2 ± 5.1 and 3.5 ± 2.6; P   =  0.473) or the distribution of embryo age at cryopreservation ( P   =  0.576). All morphokinetic parameters evaluated by time-lapse imaging, as well as the morphological characteristics, were comparable for the embryos in all three groups. Conclusions: Testosterone exposure among transgender men has no adverse impact upon fertilization rates or preimplantation embryo development and quality.